Side-group engineering of semiconducting naphthalene diimide derivatives with high solution-processability and high thermal stability - Lee, Jong Bum; Oh, Byeong M.; Lee, Yun Sang; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Kim, Jong H.; Kwon, O. Pil (Organic Electronics, 2022)
A series of new naphthalene diimide (NDI) semiconducting derivatives with different N-phenyl bicyclic side groups were rationally designed and synthesized in this study. The solubility of the orthogonal-shaped NDI derivatives with 5-tetralinyl and 4-indanyl side groups was found to be up to two orders of magnitude higher than that of the linear-shaped NDI derivatives with 6-tetralinyl and 5-indanyl side groups. The orthogonal-shaped NDI derivative with a 5-tetralinyl side group exhibited excellent solution processability due to its high solubility (e.g., 4 g/100 g dichlorobenzene), high thermal stability (e.g., lowest phase transition temperature of 380 °C), and high vertical carrier mobility (e.g., space-current-limited-current electron mobility of 7 × 10−5 cm2/V·s). Therefore, the introduction of N-phenyl bicyclic side groups on organic semiconductors was confirmed to be a highly promising design strategy for achieving the desired physical properties.
Keywords: 'current; High solubility; High thermal stability; Naphthalene diimide; Orders of magnitude; Side groups; Side-chain engineering; Side-chains; Solution processability; Synthesised; Naphthalene diimide; Organic semiconductors; Side-chain engineering; Solution processability